The PHPA/BirdLife International -Indonesia Programme: Goals and Approaches - Jepson, Paul (KUKILA, 1995)
The PHPA/BirdLife-Indonesia Programme (IP) is a collaborative conservation programme between the Ministry of Forestry, Directorate General of Forest Protection and Nature Conservation (PHPA) and BirdLife International, formalised in an Agreement approved by the Secretariat Kabinet, Republic of Indonesia, This paper provides a brief digest of the goals, structure, approaches and activities of the programme.